Complete mitochondrial genome sequence of the Sichuan digging frog Kaloula rugifera (Anura: Microhylidae). (4th March 2017) - Jiang, Lichun; Zhao, Li; Shuai, Xiaoling; Ren, Zhilin; Shen, Han; Liu, Fuchun; Ruan, Qiping; Chen, Wei
Abstract: The Sichuan Digging Frog ( Kaloula rugifera ) belongs to the family Dicroglossidae, which is endemic to northeastern Sichuan and southernmost Gansu provinces, in southwestern China. In this study, the complete mitochondrial genome of K. rugifera was sequenced. The mitogenome was 17 074 bp in length, consisting of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a non-coding control region. As in other vertebrates, most mitochondrial genes are encoded on the heavy strand, except for ND6 and eight tRNA genes which are encoded on the light strand. The overall base composition of the K. rugifera is 29.7% A, 30.3% T, 25.8% C, and 14.2% G. The alignment of the Kaloula species control regions exhibited high genetic variability and rich A + T content. Phylogenetic tree demonstrated that K. rugifera was clustered together with K. borealis and K. verrucosa and they had a close relationship with each other. The complete mitogenome of K. rugifera can provide an important data for the studies on phylogenetic relationship to further explore the taxonomic status of Kaloula species.